Metodologia ativa: analisar o papel do projeto integrador no processo ensino/aprendizagem dos alunos dos cursos técnicos na modalidade subsequente do Instituto Federal de Educação, Ciências e Tecnologia no município de Oiapoque-AP - MIRANDA, Lidiane de Vilhena Amanajás (Instituto Federal do Amapá, 2021)
One of the main issues related to the teacher's performance refers to the relationship between teaching and learning, and the types of methodologies used in the classroom; doing if necessary to verify the effectiveness and efficiency of teaching practices in these processes. We opted for bibliographic review research through an experience report, for the understanding of the educational process, the construction of knowledge and the application of active methodologies in an interdisciplinary and contextualized perspective in teaching, through the development of an integrative project. the construction and implementation of participatory models of teaching and learning with active methodologies, in which students of the Subsequent course of the Federal Institute of Education of Amapá - IFAP, Advanced Campus Oiapoque experienced these new technologies and participated in this process, increasing their skills of reflection, to see and interpret the world, to analyze it, with project experimentation and management as facilitators, expanding their knowledge beyond with notions of citizenship and social responsibility. Therefore, this proposal was attentive to the skills, needs, experiences experienced by the student and it is necessary that other methods help and facilitate the understanding of the content, for the proper understanding of those involved.